Productivity measurement III : global measurement of productivity for international comparisons at branch of industry level - an enquiry into the availability & sustainability of statistics for this purpose in O.E.C.D. member countries - Organisation for Economic Co-operation and Development (Paris : Productivity Measurement Advisory service of the OECD, 1966)
The approach to this study - international comparisons of productivity by industries took full cognizance of the fact that the problems are considerable. These problems have been accentuated, although measurement was considerably facilitated by the more or less general adoption of the concept of value added as the numerator of the ratio measure of productivity and the limitation of the denominator to labour input.
includes monograph
II 17/01/2019
Loans
Keywords: Labor productivity; Productivity measurement